MENYIKAPI KEAMANAN SIBER BAGI WARGA NEGARA DAN PERTAHANAN NEGARA DI ERA SOCIETY 5.0 - Alven Henas Orlando; Fatma Ulfatun Najicha (Prodi PPKn Universitas Slamet Riyadi, 2026)
In the development of increasingly advanced technology, the term society 5.0 has emerged. In society 5.0, people are expected to utilize technology in every aspect of their lives. With the development of advanced technology, there is a threat of cyberattacks that can take over computer systems or retrieve data unlawfully. So in responding to this, action is needed from the community and the government. People need to understand all forms of cyberattacks and their impact. And people need to protect themselves from cyberattacks. Not only the community, the government have a role in protecting population data and other sensitive data. In this case, the government needs to take preventive measures and strengthen the country's cyber security system.